Routing protocol based on genetic algorithm for energy harvesting‐wireless sensor networks. Issue 2 (1st June 2013) - Wu, Yin; Liu, Wenbo
Abstract : Traditional routing protocols are no longer suitable for the energy harvesting‐wireless sensor networks (EH‐WSN), which is powered by the energy harvested from environment instead of batteries. Rather than minimising the energy consumption and maximising the network lifetime, the main challenge in EH‐WSN is to maximise its working performance under energy harvesting constraints. In this study, the authors propose a centralised power efficient routing algorithm energy harvesting genetic‐based unequal clustering‐optimal adaptive performance routing algorithm (EHGUC‐OAPR) which contains two parts: (i) energy harvesting genetic‐based unequal clustering algorithm EHGUC and (ii) optimal adaptive performance routing algorithm (OAPR). First, the base station (BS) uses EHGUC algorithm to form clusters of unequal size and select associated cluster heads, in which the clusters closer to the BS have smaller size. Then, the BS adopts OAPR algorithm to construct an optimal routing among each cluster heads. The numerical results show that EHGUC‐OAPR is not only well applied to EH‐WSN, but also has a great improvement in network energy balance and data delivery ratio.